Singular value decomposition: computation and applications to robotics - Klein, Charles A., author; Maciejewski, Anthony A., author; Massachusetts Institute of Technology, publisher (Colorado State University. Libraries, 1989)
The singular value decomposition has been extensivelv used for the analysis of the kinematic and dynamic characteristics of robotic manipulators. Due to a reputation for being numerically expensive to compute, however, it has not been used for real-time applications. This work illustrates a formulation for the singular value decomposition that takes advantage of the nature of robotics matrix calculations to obtain a computationally feasible algorithm. Several applications, including the control of redundant manipulators and the optimization of dexterity, are discussed. A detailed illustration of the use of the singular value decomposition to deal with the general problem of singularities is also presented.
Keywords: singularities; robotic manipulators; singular value decomposition (SVD)